The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/nau.24235
|View full text |Cite
|
Sign up to set email alerts
|

Continuous vs stepwise anal acoustic reflectometry: An improved technique for physiological measurement of anal sphincter function?

Abstract: Background: Anal acoustic reflectometry (AAR) is a technique for measuring the physiological profile of the anal canal, primarily the internal anal sphincter. Evaluation of a new continuous method, recently developed for the urethra, would enable its future application for investigation of rectal reflexes. Methods: Patients aged 18 and over with fecal incontinence (FI) were included. Stepwise AAR parameters were compared with continuous opening pressure (Op, cmH 2 O), opening elastance (Oe, cmH 2 O/mm 2 ), clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…This study describes a novel method for measurement of the RAIR, a physiological parameter which previously has only been measured successfully using anorectal manometry. Our previous work developed the continuous AAR method [9] and confirmed that the rectal balloon catheter has no significant effect on the measured parameters [10]. Measured manometry parameters, however, have been shown to be affected by the diameter of the catheter [5], but this new method allows for evaluation of rectal reflexes through minimal instrumentation of the anal canal.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study describes a novel method for measurement of the RAIR, a physiological parameter which previously has only been measured successfully using anorectal manometry. Our previous work developed the continuous AAR method [9] and confirmed that the rectal balloon catheter has no significant effect on the measured parameters [10]. Measured manometry parameters, however, have been shown to be affected by the diameter of the catheter [5], but this new method allows for evaluation of rectal reflexes through minimal instrumentation of the anal canal.…”
Section: Discussionmentioning
confidence: 99%
“…(Credit: Helen Carruthers). Table 1 Anal acoustic reflectometry (AAR) parameters measure during the recto-anal inhibitory reflex (table previously described by Heywood et al [9]).…”
Section: Data Collection and Statistical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Two sets of measurements were recorded: 'baseline' (before placement of the rectal balloon catheter) and 'catheter' (after placement of rectal balloon catheter). The AAR parameters have been described before [10] and include five parameters at rest and two during voluntary squeeze ( Table 1).…”
Section: Measured Aar Parametersmentioning
confidence: 99%
“…The current method for measuring the RAIR uses a rectal balloon mounted on a manometry catheter to simultaneously measure the changes in anal canal pressure during rectal distension [8,9]. A new improved AAR technique now allows for measurements to be taken continuously [10,11]; however, due to the configuration of the AAR catheter, it is not possible to mount a rectal balloon at its end. Therefore, for the RAIR to be measured using AAR, a rectal balloon, mounted on a fine catheter, has to be placed alongside the AAR measurement catheter.…”
Section: Introductionmentioning
confidence: 99%